SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Explaining global variation in life-cycle greenhouse gas (GHG) emissions from soybeans and soybean meal: a systematic review - Nathaniel P. Springer; Pedro E. Urriola; Rylie E.O. Pelton; Aurup Ratan Dhar; Jennifer Schmitt; Gerald C. Shurson (Agricultural Systems, 2026)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Spatiotemporal Dynamics of Non‐Ecological Speciation in Rubyspot Damselflies ( Hetaerina spp.) - C. Patterson; A. Brennan; H. Cowling; A. González‐Rodríguez; G. F. Grether; L. Mendoza Cuenca; M. Springer; Y. M. Vega‐Sánchez; J. Drury (Molecular Ecology, 2025)
Non‐ecological speciation is a common mode of speciation, which occurs when allopatric lineages diverge in the absence of pronounced ecological differences. Yet, relative to other speciation mechanisms, non‐ecological speciation remains understudied. Numerous damselfly clades are characterised as non‐adaptive radiations (the result of several rounds of non‐ecological speciation without subsequent divergence), but there are few damselfly lineages for which we have a detailed understanding of the spatiotemporal dynamics of divergence. Recent phylogeographic analyses demonstrate that American rubyspot damselflies ( Hetaerina americana sensu lato) actually comprise at least two cryptic lineages that coexist sympatrically across most of Mexico. To broaden our understanding of the dynamics of diversification to other rubyspot lineages, we investigated the phylogeographic history of smoky rubyspot damselflies ( Hetaerina titia ) using genomic data collected across Central and North America. Unexpectedly, we found evidence of reproductive isolation between the highly genetically differentiated Pacific and Atlantic lineages of H. titia in a narrow secondary contact zone on the Isthmus of Tehuantepec, Mexico. We then fit models of historical demography to both H. americana sensu lato and H. titia to place these comparisons in a temporal context. Our findings indicate that Pacific and Atlantic lineages of H. titia split more recently than the broadly sympatric lineages within H. americana sensu lato, supporting key assumptions of the non‐ecological speciation model and demonstrating that these two pairs of sister lineages are at different stages of the speciation cycle.

The effects of ostarine on clinical health parameters in adult horses - C. Nealon; A.C. Herbst; S.H. White-Springer; K. Malinowski; K.H. McKeever (Journal of Equine Veterinary Science, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Identifying the stand properties that support both high biodiversity and carbon storage in German forests - K. Springer; P. Manning; A.L. Boesing; C. Ammer; A.M. Fiore-Donno; M. Fischer; K. Goldmann; G. Le Provost; J. Overmann; L. Ruess; I. Schöning; S. Seibold; et al. (Forest Ecology and Management, 2024)

Acquisition of elemental sulfur by sulfur‐oxidising Sulfolobales - Maria C. Fernandes‐Martins; Carli Springer; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2024)
Elemental sulfur (S 8 0 )‐oxidising Sulfolobales (Archaea) dominate high‐temperature acidic hot springs (>80°C, pH 8 0 ‐oxidising members of the Sulfolobales reveal a patchy distribution of genes encoding sulfur oxygenase reductase (SOR), an S 8 0 disproportionating enzyme attributed to S 8 0 oxidation. Here, we report the S 8 0 ‐dependent growth of two Sulfolobales strains previously isolated from acidic hot springs in Yellowstone National Park, one of which associated with bulk S 8 0 during growth and one that did not. The genomes of each strain encoded different sulfur metabolism enzymes, with only one encoding SOR. Dialysis membrane experiments showed that direct contact is not required for S 8 0 oxidation in the SOR‐encoding strain. This is attributed to the generation of hydrogen sulfide (H 2 S) from S 8 0 disproportionation that can diffuse out of the cell to solubilise bulk S 8 0 to form soluble polysulfides (S x 2− ) and/or S 8 0 nanoparticles that readily diffuse across dialysis membranes. The Sulfolobales strain lacking SOR required direct contact to oxidise S 8 0 , which could be overcome by the addition of H 2 S. High concentrations of S 8 0 inhibited the growth of both strains. These results implicate alternative strategies to acquire and metabolise sulfur in Sulfolobales and have implications for their distribution and ecology in their hot spring habitats.

Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

59 Inter-rater reliability of equine nutrition screening tools in a clinical setting - A. Self; M.T. Hines; C. Springer; L.G. Strickland; K. McCormick; J.L.-Z. Ivey (Journal of Equine Veterinary Science, 2023)

55 Impacts of dietary Protandim Nrf2 Synergizer on antioxidant status of mature, sedentary horses - P.L. Semanchik; L.T. Wesolowski; J.L. Simons; R.L. Seward; C. Beer; E.D. Barnes; S.H. White-Springer (Journal of Equine Veterinary Science, 2023)

Cover and density of southwestern ponderosa pine understory plants in permanent chart quadrats (2002–2020) - Margaret M. Moore; Jeffrey S. Jenness; Daniel C. Laughlin; Robert T. Strahan; Jonathan D. Bakker; Helen E. Dowling; Judith D. Springer (Ecology, 2022)
This data set consists of 101 permanent 1 m × 1 m (1‐m 2 ) quadrats located within southwestern ponderosa pine ecosystems near Flagstaff, Arizona, USA. Individual plants in these quadrats were identified and mapped annually for 19 years (2002–2020). The original chart quadrats were established between 1912 and 1927 to determine the effects of domestic livestock grazing on herbaceous plants and pine seedlings. Today these data provide opportunities to examine the effects of climate and land‐use change on plant demography, population dynamics, and community processes. We provide the following data and data formats: (1) digitized maps of all plant locations in shapefile and geodatabase format, (2) shapefiles showing annual locations of each individual plant species, (3) annual maps of each quadrat in TIFF and PDF format, (4) annual basal area of each species per quadrat for species mapped as polygons, (5) tabular representation of polygon areas and centroid locations for plant species mapped as polygons, (6) tabular representation of point locations for plant species mapped as points, (7) plot‐scale 20 m × 20 m overstory tree canopy cover, tree basal area, parent material, and elevation, (8) quadrat‐scale information (e.g., quadrat site and number, coordinates in UTM Zone 12 and latitude/longitude, and descriptive comments for each quadrat), (9) plant species list, (10) summary of plant species observed in each quadrat, (11) summary of quadrats mapped by site and year, and (12) data formatted for use in Integral Projection Models (IPM) and plant population analyses. There are no copyright restrictions; please cite this paper and the associated data set when data are used in publications.

Correction to: Characterizing introgression‑by‑environment interactions using maize near isogenic lines - Zhi Li; Sara B. Tirado; Dnyaneshwar C. Kadam; Lisa Coffey; Nathan D. Miller; Edgar P. Spalding; Aaron J. Lorenz; Natalia de Leon; Shawn M. Kaeppler; Patrick S. Schnable; Nathan M. Springer; Candice N. Hirsch (Theoretical and Applied Genetics, 2021)

Jamaican bioethanol: an environmental and economic life cycle assessment - E. Batuecas; R. Contreras-Lisperguer; C. Mayo; R. Díaz; C. Springer; F. J. Pérez (Clean Technologies and Environmental Policy, 2021)

The clinical and educational outcomes of an inter-professional student-led medication review team, a pilot study - Michael O. Reumerman; Milan C. Richir; Philippe M. Domela Nieuwenhuis; Rowan Sultan; Hester E. M. Daelmans; Hans Springer; Majon Muller; Michiel A. van Agtmael; Jelle Tichelaar (European Journal of Clinical Pharmacology, 2021)
Aims The involvement of an inter-professional healthcare student team in the review of medications used by geriatric patients could not only provide patients with optimized therapy but also provide students with a valuable inter-professional learning experience. We describe and evaluate the clinical and learning outcomes of an inter-professional student-run mediation review program (ISP). Subject and method A variable team consisting of students in medicine, pharmacy, master advanced nursing practice, and master physician assistant reviewed the medication lists of patients attending a specialized geriatric outpatient clinic. Results During 32 outpatient visits, 188 medications were reviewed. The students identified 14 medication-related problems, of which 4 were not recognized by healthcare professionals. The ISP team advised 95 medication changes, of which 68 (71.6%) were directly implemented. Students evaluated this pilot program positively and considered it educational (median score 4 out of 5) and thought it would contribute to their future inter-professional relationships. Conclusion An inter-professional team of healthcare students is an innovative healthcare improvement for (academic) hospitals to increase medication safety. Most formulated advices were directly incorporated in daily practice and could prevent future medication-related harm. The ISP also offers students a first opportunity to work in an inter-professional manner and get insight into the perspectives and qualities of their future colleagues.

Characterizing introgression-by-environment interactions using maize near isogenic lines - Zhi Li; Sara B. Tirado; Dnyaneshwar C. Kadam; Lisa Coffey; Nathan D. Miller; Edgar P. Spalding; Aaron J. Lorenz; Natalia de Leon; Shawn M. Kaeppler; Patrick S. Schnable; Nathan M. Springer; Candice N. Hirsch (Theoretical and Applied Genetics, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

E-vapor aerosols do not compromise bone integrity relative to cigarette smoke after 6-month inhalation in an ApoE–/– mouse model - Marie K. Reumann; Jenny Schaefer; Bjoern Titz; Romina H. Aspera-Werz; Ee Tsin Wong; Justyna Szostak; Victor Häussling; Sabrina Ehnert; Patrice Leroy; Wei Teck Tan; Arkadiusz Kuczaj; Christof Audretsch; et al. (Archives of Toxicology, 2020)
Cigarette smoke (CS) exposure is one of the leading risk factors for human health. Nicotine-containing inhalable products, such as e-cigarettes, can effectively support tobacco harm reduction approaches. However, there are limited comparative data on the effects of the aerosols generated from electronic vapor products (e-vapor) and CS on bone. Here, we report the effects of e-vapor aerosols and CS on bone morphology, structure, and strength in a 6-month inhalation study. Eight-week-old ApoE –/– mice were exposed to aerosols from three different e-vapor formulations—CARRIER (propylene glycol and vegetable glycerol), BASE (CARRIER and nicotine), TEST (BASE and flavor)—to CS from 3R4F reference cigarettes at matched nicotine concentrations (35 µg/L) or to fresh air (Sham) ( N = 10 per group). Tibiae were analyzed for bone morphology by µCT imaging, biomechanics by three-point bending, and by histological analysis. CS inhalation caused a significant decrease in cortical and total bone volume fraction and bone density relative to e-vapor aerosols. Additionally, CS exposure caused a decrease in ultimate load and stiffness. In contrast, bone structural and biomechanical parameters were not significantly affected by e-vapor aerosol or Sham exposure. At the dissection time point, there was no significant difference in body weight or tibia bone weight or length among the groups. Histological findings revealed microcracks in cortical bone areas among all exposed groups compared to Sham control. In conclusion, because of the bone-preserving effect of e-vapor aerosols relative to CS exposure, e-vapor products could potentially constitute less harmful alternatives to cigarettes in situations in which bone health is of importance.

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Erratum to: Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Antagonism of brain insulin-like growth factor-1 receptors blocks estradiol effects on memory and levels of hippocampal synaptic proteins in ovariectomized rats - Britta S. Nelson; Rachel C. Springer; Jill M. Daniel (Psychopharmacology, 2014)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

Soil aggregation and carbon sequestration are tightly correlated with the abundance of arbuscular mycorrhizal fungi: results from long‐term field experiments - Gail W. T. Wilson; Charles W. Rice; Matthias C. Rillig; Adam Springer; David C. Hartnett (Ecology Letters, 2009)
We examined the role of arbuscular mycorrhizal fungi (AMF) in ecosystems using soil aggregate stability and C and N storage as representative ecosystem processes. We utilized a wide gradient in AMF abundance, obtained through long‐term (17 and 6 years) large‐scale field manipulations. Burning and N‐fertilization increased soil AMF hyphae, glomalin‐related soil protein (GRSP) pools and water‐stable macroaggregates while fungicide applications reduced AMF hyphae, GRSP and water‐stable macroaggregates. We found that AMF abundance was a surprisingly dominant factor explaining the vast majority of variability in soil aggregation. This experimental field study, involving long‐term diverse management practices of native multispecies prairie communities, invariably showed a close positive correlation between AMF hyphal abundance and soil aggregation, and C and N sequestration. This highly significant linear correlation suggests there are serious consequences to the loss of AMF from ecosystems.

Epibiotic bacteria associated with the recently discovered Yeti crab, Kiwa hirsuta - Shana K. Goffredi; William J. Jones; Hermann Erhlich; Armin Springer; Robert C. Vrijenhoek (Environmental Microbiology, 2008)
Summary The Yeti crab, Kiwa hirsuta Macpherson et al. , is the single known species in a recently discovered crab family Kiwaidae ( Decapoda : Galatheoidea ) from deep‐sea hydrothermal vents. Its chelipeds, walking legs and the ventral surface of its cephalothorax are covered with dense setae that, in turn, are covered with clusters of filamentous bacteria, making the crab appear extraordinarily ‘hairy’. Electron microscopy revealed dense bacterial clusters attached to the chitinous outer layer of the setae. Molecular phylogenetic analyses revealed the setae‐associated bacteria to be dominated by ε‐ Proteobacteria (∼56% of the recovered ribotypes), γ‐ Proteobacteria (∼25%) and Bacteroidetes (∼10%). Fluorescence in situ microscopy confirmed the attachment of filamentous ε‐ Proteobacteria on setae, but no specialized morphological structures appeared to exist for bacterial attachment. Key enzymes involved in the reductive tricarboxylic acid cycle (ATP‐dependent citrate lyase) and sulfite oxidation or dissimilatory sulfate reduction (bidirectional APS reductase) were detected. Consequently, the potential for carbon fixation and cycling of reduced and oxidized sulfur appear to exist in the dense microflora that grows on the crab's setae.

Tracing carbon flow in an arctic marine food web using fatty acid-stable isotope analysis - S. M. Budge; M. J. Wooller; A. M. Springer; S. J. Iverson; C. P. McRoy; G. J. Divoky (Oecologia, 2008)

Restoring plant species diversity and community composition in a ponderosa pine-bunchgrass ecosystem - Daniel C. Laughlin; Jonathan D. Bakker; Mark L. Daniels; Margaret M. Moore; Cheryl A. Casey; Judith D. Springer (Plant Ecology, 2008)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Structure–activity relationships in platinum–acridinylthiourea conjugates: effect of the thiourea nonleaving group on drug stability, nucleobase affinity, and in vitro cytotoxicity - Margaret C. Ackley; Colin G. Barry; Amanda M. Mounce; Michael C. Farmer; Beth-Erin Springer; Cynthia S. Day; Marcus W. Wright; Susan J. Berners-Price; Suzanne M. Hess; Ulrich Bierbach (JBIC Journal of Biological Inorganic Chemistry, 2004)

Molecular Relationships of the New Guinean Bandicoot Genera Microperoryctes and Echymipera (Marsupialia: Peramelina) - M. Westerman; M. S. Springer; C. Krajewski (Journal of Mammalian Evolution, 2001)

Cervical lymphadenitis due to an unusual mycobacterium - E. Tortoli; P. Kirschner; B. Springer; A. Bartoloni; C. Burrini; A. Mantella; M. Scagnelli; C. Scarparo; M. T. Simonetti; E. C. Böttger (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Sex-limited genetic variation in a mouse salivary protein - Robert C. Karn; Stephen R. Dlouhy; Kenneth R. Springer; J. Peter Hjorth; J. Tnnes Nielsen (Biochemical Genetics, 1982)